The switch - Horowitz, Anthony (Walker London, 2004)
The author of 'Granny' has produced a thrilling action-packed story, a kind of 'Trading Places' for kids, where Tad, the boy who has everything, wakes up as Bob Snarby in the shabbiest funfair imaginable.